Achieving Health Outcomes in Colombia : Civil Registration and Vital Statistics System, Unique Personal Identification Number, and Unified Beneficiary Registry System for Births and Deaths - Toro Roa, Juan Pablo; Iunes, Roberto F.; Mills, Samuel (World Bank, Washington, DC, 2019)
This case study on Colombia describes how the civil registration and national identification system and the health information system have facilitated progress toward universal health coverage. The study includes a description of Colombia’s General Social Health Insurance System (Sistema General de Seguridad Social en Salud [SGSSS]), assignment of a unique personal identification number (UPIN) at birth, and the interoperability of the civil registration and health information systems. It explains how the civil registration system and the UPIN have helped improve health outcomes and explains the role of death registration. The study finishes with conclusions, lessons learned, and recommendations. A brief overview of Colombia is presented in Annex 1. This study focuses on identification of and access to health services, which are considered rights in Colombia. This report emphasizes the importance of establishing an individual’s legal identity in childhood to facilitate early access to social and other services and for greater accuracy in population statistics.